The Optimal Taxation of Couples - Mikhail Golosov; Ilia Krasikov (The Quarterly Journal of Economics, 2025)
ABSTRACT We study optimal nonlinear taxation of single and married households. Taxes on couples depend on the earnings of both spouses and are an example of multidimensional tax schedules. We develop novel analytical techniques to study properties of such taxes. We show that the optimal marginal taxes for married individuals are generally lower than for single individuals because resource sharing in couples provides socially valuable redistribution. Under realistic assumptions, the optimal tax rates for married individuals increase with the correlation of spousal earnings, the marginal tax rates for one spouse increase (decrease) in the earnings of the other if both spouses have low (high) earnings, and the primary earner faces lower marginal taxes than the secondary earner.